Pengaruh Keadilan Distributif dan Prosedural terhadap Kepuasan Kerja Tenaga Kependidikan Non Pegawai Negeri Sipil (Non PNS) di Universitas Brawijaya - Indra Heavyantono, Okky (Jurnal Ilmiah Administrasi Publik, 2018)
The objective of this research study is to examine the effect of distributive and procedural justice on job satisfaction through perceived organizational support among academic staff in Brawijaya University. Data collected from questionnaire and analyzed with PLS-based SEM techniques with conceptual model are developed from literature and empirical study. The result of the analysis shows both distributive justice and procedural justice were found to be significantly and directly related to perceived organizational support, but no direct sgnificant effecton job satisfaction. Furthermore, not only an academic staffs must be treated fairly enough, but also must be feeling supported from their organization to get them more satisfied in their job.